Letter (copy) - Squance, W. J. R.
034-0076-001 Telegraphic Address "Aslocobrom, Haver, London" Telephone No HAMPSTEAD 6300 Associated Society of Locomotive Engineers and Firemen, 9 Arkwright Road, Hampstead, London N.W.3. TRADE UNION No. 348 T. APPROVED SOCIETY No. 253. W.J.R. SQUANCE GENERAL SECRETARY W. P. ALLEN ASSISTANT GENERAL SECRETARY NOTE. For each subject—a separate letter . DS. Mrs, C. Haldane, Hon. Sec. International Brigade, National Memorial Fund, 1, Litchfield Street, Charing Cross, London, W.C.2. Ack by p.c. receiving attention 6/5/39. 9th May, 1939. Dear Madam, With reference to your letter of the 27th ultimo and previous correspondence I may say that my Executive Committee have seriously considered your many appeals but find themselves restricted so far as the funds of the Society are concerned but in view of the financial assistance required by the Wounded and Dependants Aid Committee they have decided that the balance of the International Solidarity Fund be devoted for this purpose. I have therefore pleasure in enclosing cheque value £30. 0. 0. which please acknowledge in the usual way. Yours sincerely, W.J.R. Squance GENERAL SECRETARY. Sir Walter Citrine, K.B.E., General Secretary, Trades Union Congress, Transport House London, S.W.1. COPY FOR YOUR INFORMATION. 292/946/34/76